Impact of the Poor Oral Health Status of Children on Their Families: An Analytical Cross-Sectional Study - Mir Faeq Ali Quadri; Fatimah Rasheed M. Jaafari; Noha Ahmed A. Mathmi; Nouf Hassan F. Huraysi; Maryam Nayeem; Abbas Jessani; Santosh Kumar Tadakamadla; Jyothi Tadakamadla (MDPI AG, 2021)
The impact of poor oral health may not just be limited to the children themselves but can impact their families. The current study aims to perform psychometric analyses of the Arabic version of the Family Impact Scale and investigate the association of its domains with the oral health status of children. This cross-sectional study was carried out in a sample of 500 parent-child dyads from high schools of Jazan city of the Kingdom of Saudi Arabia. The Arabic version of the Family Impact Scale was subjected to reliability and validity tests. The explanatory variables in the current study are: the oral health status, parents combined income, parents' education, age and sex of the child. The descriptive analysis was reported using proportions, this was followed by the bivariate and multivariable analyses. About 24.2% of children were reported to have fair, poor, and very poor oral health. A lower frequency of family impact corresponded with better oral health (OH) status of children (p < 0.001). The likelihood of parent's taking time off from work and having financial difficulties was nearly two-times greater if their children had poor oral health. Similarly, interruption in sleep and other normal activities of parents is four times and five times greater, respectively, if the child has poor oral health status. Thus, the poor oral health of school children in the Jazan region of Saudi Arabia is a matter of grave concern as it is observed to be associated with family impacts; particularly affecting the parent's work, sleep, and other normal family activities.